State Physical Education Policy Changes From 2001 to 2016 - Dauenhauer, Brian; Keating, Xiaofen; Stoepker, Peter; Knipe, Robert (Journal of School Health, 2019)
ABSTRACT BACKGROUND State policies influence the quantity and quality of educational programs delivered in schools. This study examined state physical education policy changes from 2001 to 2016 by analyzing data reported in The Shape of the Nation Report . METHODS Policies related to state mandates for physical education, time/credit requirements, assessment and fitness testing requirements, adoption of state standards, and allowance of substitutions were analyzed over 5 editions of the report using repeated measures statistics. RESULTS A majority of state physical education‐related policies have not changed over the past 15 years despite calls by numerous public health agencies for enhanced physical education in schools. There was, however, a significant increase in the number of states adopting teaching standards and requiring assessment and fitness testing in physical education, mirroring a broader shift in education toward standards, assessment, and accountability. CONCLUSIONS Despite improved rigor in physical education through the adoption of standards and assessment practices, physical education continues to be marginalized in schools by a lack of curricular time and inappropriate substitution policies. Stronger policies are needed for physical education to have a substantial impact on school health.
Keywords: dept.hms; peer-reviewed

Championing CSPAPs: studies of targeted program implementers and advocates - Webster, Collin A.; Moore, Chanta; Orendorff, Karie Lee; Taunton, Sally; Mindrila, Diana; Stewart, Gregory; Lee, Joey A.; Welk, Gregory J.; Foster, Lorraine Lanningham; Gentile, Douglas; Vazou, Spyridoula; Liechty, Laura; et al. (Research Quarterly for Exercise and Sport, 2019)
Keywords: dept.hms; peer-reviewed; ⛔ No DOI found